Electroclinical features of seizures associated with autoimmune encephalitis. (August 2018) - Steriade, Claude; Moosa, Ahsan N.V.; Hantus, Stephen; Prayson, Richard A.; Alexopoulos, Andreas; Rae-Grant, Alexander
Highlights: Autoimmune seizures frequently involve the medial temporal and perisylvian regions. Electroclinical features are dynamic and evolve over the course of the disease. Refractory and frequent seizures are seen in the acute phase. In patients who continue to experience seizures, no latent period is seen. Electroclinical features involving temporal lobes predict persistence of seizures. Abstract: Purpose: We sought to characterize the electroclinical features of seizures associated with autoimmune encephalitis and their relevance to outcome. Methods: 19 patients with seizures and autoimmune encephalitis were identified from a database of 100 patients (2008–2017) with autoimmune neurological disorders. Clinical and electroclinical characteristics were collected. Persistent seizures at last follow-up were then correlated with electroclinical features. Results: Status epilepticus (53%) and early intractability to AEDs (median time to second AED 9.5 days) marked the onset of refractory seizures (median number of AEDs 3). Seizure semiology (abdominal (16%), psychic (42%), olfactory (6%) auras), interictal temporal epileptiform discharges (42%), and ictal onset in the temporal region (63%) mirrored radiologic involvement of the medial temporal regions (on MRI in 74% and/or FDG-PET in 75%). In addition, multimodal auras, with somatosensory (26%), autonomic (26%), gustatory (11%), and visual (16%), features were seen in 82% of patients with focal aware seizures, invoking broader involvement of the perisylvian regions. A change in seizure semiology and EEG findings was often seen. Electroclinical features were similar regardless of antibody type, with the exception of the association of faciobrachial dystonic seizures with LGI1 antibodies. Eight patients had medically intractable seizures at last follow-up and were more likely than patients with seizure remission to have generalized tonic-clonic seizures and temporal lobe involvement on the basis of semiological features, interictal EEG and MRI changes. Conclusions: Seizures associated with autoimmune encephalitis exhibit common electroclinical features which show dynamic evolution over time. We propose a role for the temporo-perisylvian regions in their generation.